The Ten Perfections of the Bodhisattva (Dasa Pāramī): Principles for Application towards a Peaceful Society - Denis, Sirinnard (Journal of Buddhist Innovation Review, 2026)
This academic article presents the application of the Ten Perfections (Dasa Pāramī) in contemporary society through a synthesis of Buddhist scriptures and related academic literature. The study develops an integrated conceptual framework for applying the Ten Perfections in daily life, educational systems, and social institutions. The findings indicate that the Ten Perfections provide a fundamental ethical framework for fostering positive behavioral change by reducing selfishness, social inequality, and conflict while promoting generosity, responsibility, perseverance, impartiality, and wisdom in everyday life. Furthermore, integrating the Ten Perfections with the Five Precepts (Pañca-sīla) strengthens personal and social well-being by safeguarding life, property, family relationships, truthful communication, and mindfulness. This integrated ethical framework encourages peaceful coexistence, mutual respect, and non-violence, ultimately contributing to the development of a harmonious, morally grounded, and sustainable peaceful society at the individual, family, community, and societal levels.